2022
DOI: 10.6007/ijarbss/v12-i1/12151
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Learners’ Motivations for Studying From Home

Abstract: Over the last decade, online learning has grown significantly as the internet and education have merged to provide people with the possibility to learn new skills. Since the COVID-19 outbreak, online learning, or studying at home has become more centric in people's lives. The pandemic has caused schools, universities, and businesses to operate remotely, which has increased the use of online learning. Foreign language learning is also no exception. The purpose of this survey is to find out how students feel abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…These can be attributed to a lack of interpersonal relationships with lecturers. This is supported by a study by Ahmad et al (2021) that found during online learning, students were found to experience ample attention from the lecturers. Hence, it is suggested that students build good interpersonal relationships with the lecturers gives the students a sense of relatedness that motivates their learning.…”
Section: Summary Of Findings and Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…These can be attributed to a lack of interpersonal relationships with lecturers. This is supported by a study by Ahmad et al (2021) that found during online learning, students were found to experience ample attention from the lecturers. Hence, it is suggested that students build good interpersonal relationships with the lecturers gives the students a sense of relatedness that motivates their learning.…”
Section: Summary Of Findings and Discussionmentioning
confidence: 54%
“…Although values components are found to be more important, growth and relatedness cannot be ignored. In terms of growth, which is identified through the expectancy component, students of Universiti Teknologi MARA (UiTM) have shown their appreciation towards the flexibility of learning from home which saved commuting time though experiencing the same stress of learning (Ahmad et al, 2021). During online learning, students experience relatedness which is the affective component where they receive ample attention from the lecturers (Ahmad et.…”
Section: Motivators For Learningmentioning
confidence: 99%
“…Over the last decade, the pedagogical use of technology has emerged progressively within the education world. The Covid-19 outbreak has forced all education institutions to adopt online learning, making it the main pedagogical mode for at least two years (Ahmad et al, 2022). During the outbreak, online learning was the best way to maintain learning among students.…”
Section: Problem Statementmentioning
confidence: 99%
“…During the outbreak, online learning was the best way to maintain learning among students. Some studies have reported that it provides time and cost savings and flexible time and location to attend classes (Ahmad et al, 2022;Šestanović & Siddiqui, 2021). The flexibility provides time to adjust and deals with uncertainty for students and teachers (Abuhmaid et al, 2022).…”
Section: Problem Statementmentioning
confidence: 99%
“…Only when the sentiments of existence and relatedness are met can the person progress to Growth as Growth includes employees' desire to be more productive (Alderfer, 1969). In a study by Ahmad et al (2022), on learner's motivations for studying from home found that a learners' growth is reflected in their learning performance. The same can be said for workers as proven in the study by Abdullah et al (2020), on the views of employees working from home post COVID-19.…”
Section: Growth (Work Life Performance)mentioning
confidence: 99%